Homing behaviour and individual identification of the pipefish Nerophis lumbriciformis (Pisces; Syngnathidae): A true intertidal resident? - Monteiro, Nuno Miguel (2012)
Syngnathids have been the focus of growing interest due to their peculiar reproductive biology and vulnerability to environmental degradation and overcollecting. In this study, near the south limit of the species’ geographic distribution, a description of the homing behaviour of the worm pipefish, Nerophis lumbriciformis, based on the unique facial pigmentation patterns, is presented. Even though the amount of facial pigmentation was substantially higher in larger adult females, suggesting that it can be part of the secondary sexual repertoire of this sex role reversed species, this technique allowed for the positive identification of adult individuals (males and females) during at least 19 months. Recaptures showed that this pipefish shows a strong homing behaviour, with individuals being regularly captured within less than 2 m of the original identification event. The absence of horizontal migrations to adjacent areas and the observation of adults in the subtidal, together with the overall low number of recaptures (even though some individuals were cyclically resighted) highlighted the fact that the intertidal is not N. lumbriciformis’ permanent residence. This observation also demonstrates that the estimation of the population size, important for conservation purposes, based solely on intertidal data can be misleading because captured individuals are only a fraction of a larger, mainly subtidal, population.